2014
DOI: 10.1242/jeb.095646
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and lifetime flight behavior on flight capacity inDrosophila melanogaster

Abstract: The effects of flight behavior on physiology and senescence may be profound in insects because of the extremely high metabolic costs of flight. Flight capacity in insects decreases with age; in contrast, limiting flight behavior extends lifespan and slows the age-related loss of antioxidant capacity and accumulation of oxidative damage in flight muscles. In this study, we tested the effects of age and lifetime flight behavior on flight capacity by measuring wingbeat frequency, the ability to fly in a hypo-dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
3
16
1
1
Order By: Relevance
“…This is probably due to an inhibition in the activity of host-seeking induced by the development of the ovaries and by a mechanical stimulus induced by the deterioration of muscle structure promoted by the aging process, old females are still able to sustain some stable capacity to fly when challenged (Sohal, 1976;Rockstein and Brandt, 1963;Sacktor and Shimada, 1972). These results agree with the known consequences of aging on flight capacity of different insect species (Williams et a., 1943, Lane et al, 2014Margotta et al, 2018;Dingle, 1965;Wigglesworth, 1949;Williams et al, 1943;Rockstein and Bhatnagar, 1966;Levenbook and Williams, 1956;Tribe, 1966;Nayar and Sauerman, 1973). Although, to our knowledge, no direct effects of dietary ethanol supplementation were assessed on mosquito flight capacity, an interesting study revealed that ethanol and trimethylglycine (beer components) and beer itself, exhibited protective effects to mosquitoes against ionizing radiation (Rodriguez et al, 2013).…”
Section: Resultssupporting
confidence: 80%
“…This is probably due to an inhibition in the activity of host-seeking induced by the development of the ovaries and by a mechanical stimulus induced by the deterioration of muscle structure promoted by the aging process, old females are still able to sustain some stable capacity to fly when challenged (Sohal, 1976;Rockstein and Brandt, 1963;Sacktor and Shimada, 1972). These results agree with the known consequences of aging on flight capacity of different insect species (Williams et a., 1943, Lane et al, 2014Margotta et al, 2018;Dingle, 1965;Wigglesworth, 1949;Williams et al, 1943;Rockstein and Bhatnagar, 1966;Levenbook and Williams, 1956;Tribe, 1966;Nayar and Sauerman, 1973). Although, to our knowledge, no direct effects of dietary ethanol supplementation were assessed on mosquito flight capacity, an interesting study revealed that ethanol and trimethylglycine (beer components) and beer itself, exhibited protective effects to mosquitoes against ionizing radiation (Rodriguez et al, 2013).…”
Section: Resultssupporting
confidence: 80%
“…For each test temperature, two rounds of assessment were performed across 3 days. Consequently, for each test temperature, two rounds of egg picking (1 week apart) were performed to minimise age differences of the focal flies (Lane et al, 2014;Terblanche et al, 2004). On each of the 3 days, two runs were performed in the morning and the afternoon (time of experiment in analyses), always at the same time to limit the effects of circadian rhythm on estimates of SMR.…”
Section: Smrmentioning
confidence: 99%
“…Flight activity may contribute to senescence when foragers accumulate more than 10 days of flight experience. In fruit flies with free access to flight in vials, mitochondrial respiration and electron transport chain activity declines with age (Ferguson et al, 2005), and forcing flight induces early metabolic and behavioral senescence (Lane et al, 2014). As foragers age, glycogen synthesis slows and eventually ceases (Neukirch, 1982), suggesting that foraging damages carbohydrate metabolism.…”
Section: Flight Induces Oxidative Damagementioning
confidence: 99%
“…Understanding how naturally occurring behaviors link lifespan and oxidative damage may reveal how activity levels influence senescence (Metcalfe and Alonso-Alvarez, 2010). While the oxidative stress model still elicits controversy in mammals, the theory appears to apply well to flying insects, especially hoverers (Yan and Sohal, 2000;Williams et al, 2008;Sohal et al, 1984;Lane et al, 2014). Behavioral manipulations and studies of longevity mutants show that age-related increases in oxidative damage and decreased protective mechanisms lead to senescence (Golden et al, 2002;Martin and Grotewiel, 2006;Sohal, 2002;Sohal and Buchan, 1981;Sohal and Dubey, 1994;Sohal et al, 1995;Sun and Tower, 1999;Sun et al, 2004;Takahashi et al, 2000;Vieira et al, 2000;Yoon et al, 2002;Yu and Chung, 2006).…”
Section: Introductionmentioning
confidence: 99%